14th-16th-Century Danube Floods and Long-Term Water-Level Changes in Archaeological and Sedimentary Evidence in The Western and Central Carpathian Basin: an Overview with Documentary Comparison - Kiss, Andrea; Laszlovszky, József (Journal of Environmental Geography, 2013)
In the present paper an overview of published and unpublished results of archaeological and sedimentary investigations, predominantly reflect on 14th-16th-century changes, are provided and evidence compared to documentary information on flood events and long-term changes. Long-term changes in flood behaviour (e.g. frequency, intensity, seasonality) and average water-level conditions had long-term detectable impacts on sedimentation and fluvio-morphological processes. Moreover, the available archaeological evidence might also provide information on the reaction of the society, in the form of changes in settlement organisation, building structures and processes. At present, information is mainly available concerning the 16th, and partly to the 14th-15th centuries. These results were compared to the available documentary evidence on 14th-16th century Danube floods occurred in the Carpathian Basin.